Algorithms of Mobile Object Location with Satellite Systems - Kluga, A. (Elektronika ir Elektrotechnika, 2005)
Comparison of tow most frequently used algorithms for mobile object place location with satellite systems is shown in this work. First is the minimum mean-square (MMS) recursive algorithm. Second is recursive Kalman filtering algorithm. Estimation of algorithms was obtained by modeling mobile object place location with satellite systems in various dynamic and noise signal situations. Is show, that no one of algorithms is working perfect in all situations and thy can be used complex in mobile systems. Ill. 5, bibl. 4 (in English, summaries in Lithuanian, English, Russian).